2012
DOI: 10.1016/j.drudis.2012.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Does transbilayer diffusion have a role in membrane transport of drugs?

Abstract: The existing consensus on coexistence of transbilayer diffusion and carrier-mediated transport as two main mechanisms for drugs crossing biological membranes was recently challenged by a systems biology group. Their transporters-only hypothesis is examined in this article using published experimental evidence. The main focus is on the key claim of their hypothesis, stating that ‘the drug molecules cross pure phospholipid bilayers through transient pores that cannot form in the bilayers of cell membranes, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Indeed, superimposition of the two molecules revealed that losartan indicates some common structural features with sarmesin (i.e., C-terminal amino acids Ile 5 -His 6 -Pro 7 -Phe 8 -COO-of sarmesin and the corresponding alkyl chain, hydroxyl methyl imidazole, spacer phenyl ring and phenyl tetrazole groups of losartan). This finding explained the rational design of losartan which is based on mimicking the C-terminal of AII [17]. The most important finding in this work was that losartan exists in two possible bioactive enantiomeric conformers as illustrated in Figure 1.…”
Section: Conformational Properties Drug Action and Stability Of At1r Antagonists In Solventsmentioning
confidence: 60%
See 1 more Smart Citation
“…Indeed, superimposition of the two molecules revealed that losartan indicates some common structural features with sarmesin (i.e., C-terminal amino acids Ile 5 -His 6 -Pro 7 -Phe 8 -COO-of sarmesin and the corresponding alkyl chain, hydroxyl methyl imidazole, spacer phenyl ring and phenyl tetrazole groups of losartan). This finding explained the rational design of losartan which is based on mimicking the C-terminal of AII [17]. The most important finding in this work was that losartan exists in two possible bioactive enantiomeric conformers as illustrated in Figure 1.…”
Section: Conformational Properties Drug Action and Stability Of At1r Antagonists In Solventsmentioning
confidence: 60%
“…Discovering the exact mechanism that the molecules use to approach their receptors could be an extremely important tool in the drug design process. The design of novel molecules should take into account, not only the binding affinity of the drugs to their receptors, but also their capacity to penetrate lipid bilayers or "survive" in the aquatic environment [17]. Moreover, many obstacles like the accumulation of drug molecules into the cellular membrane [18] could be surpassed by observing the mechanism each drug utilizes to reach its receptor's active site.…”
Section: Introductionmentioning
confidence: 99%
“…analogous to the ion trap effect that underlies weak base accumulation in lysosomes, but the compound charge is opposite and the mitochondrial matrix is alkaline (pH ~8, Trapp and Horobin, 2005, Balaz, 2012, Llopis, et al, 1998, Rossignol, et al, 2004. The ion trapping effect of organic acids in mitochondria has been modeled, where the results illustrated that ion trapping yields a positive shift in total cellular accumulation (Trapp andHorobin, 2005, Scott, et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, an apparent discontinuity exists between high passive permeability and asymmetric transporter-mediated uptake into cells in the absence and presence of an inhibitor. Furthermore, it has been noted that cellular accumulation is not necessarily evidence that accumulating drugs are actively transported (Balaz, 2012). To investigate the apparent discontinuity an analogous observation was considered from the literature.…”
Section: Introductionmentioning
confidence: 99%